Investigation of the ion-surface interaction on a liquid gallium surface under nitrogen plasma bombardment - Vasquez, Magdaleno R. (2006., 2006)
An investigation was made to determine the mechanisms involved in the ion-surface interaction on a liquid gallium (Ga) target under nitrogen (N2) plasma based on a plasma-sputter type ion source system. Scanning electron microscope images revealed two distinct surface characteristics of the target which can be either smooth or rough, while energy dispersive X-ray spectroscopy analyses revealed the elemental composition of the irradiated targets. The surface roughness of the target evolved when highly energetic ions reach the target surface, which caused the sputtering of the surface atoms. A relatively smooth surface was achieved when the target was placed near the magnetic cusp which acted as a shield, weeding out energetic ions that damaged the surface. A close inspection of a cleaved target revealed columnar growth of the crystals with preferred orientation. Crystal stoichiometry was found to be influenced by the presence of oxygen. Traces of oxygen revealed relatively large hexagonal GaN crystal with good stoichiometry. Further investigation was made by employing the Transport of Ions in Matter (TRIM) simulation tool to determine the sputtering yields of different targets, namely Ga, GaN and thin GaN layer on a Ga under nitrogen plasma bombardment. The semi-empirical Yamamura formula was used to validate TRIM's capability and reliability. It was shown that the TRIM results were in good agreement with the Yamamura formula. In addition, TRIM simulations revealed lower sputtering yield of a GaN target compared to a Ga target. TRIM simulations were also used to determine the effect of the ion angle of incidence on sputtering. An increase in the sputtering yield was observed when the angles of incidence ranged from 60° to 80° and further increased as the ion energies were increased. A general GaN growth model was developed in order to address the possible interactions between the bombarding nitrogen species and the Ga target surface. In order to implement the growth model, a modified kinetic Monte Carlo (KMC) simulation method was employed to reveal the surface characteristics of the target in the early stages of plasma exposure. Monte Carlo simulations revealed the growth of GaN, the formation of the columnar structure, the effective decrease in the sputtering yield and the rate of growth of GaN. The ion energy used in this study ranged from 50 to 1000 eV. The simulations revelated a relatively smooth surface of GaN from 50 to 100 eV ion energies and starts to roughen up to 500 eV and eventually minimal formation of GaN at 1000 eV ion energy
Introduction -- Literature review -- Methods and materials -- Surface characterization results -- Sputtering yields -- GaN growth model -- Summary of results -- Conclusions and recommendations -- References -- Appendix A. Yamamura sputtering yield formula -- Appendix B. Generation of random numbers -- Appendix C. Simulation code -- Appendix D. Record of runs -- Appendix E. Related papers.
Thesis (M.S. Materials Science and Engineering)--University of the Philippines Diliman.
Keywords: Gallium -- Analysis; Ion bombardment; Ion-atom collisions; Nitrogen plasmas